2018
DOI: 10.1007/s00381-018-3821-y
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted stereotactic brain biopsy: systematic review and bibliometric analysis

Abstract: IntroductionStereotactic brain biopsy represents one of the earliest applications of surgical robotics. The aim of the present systematic review and bibliometric analysis was to evaluate the literature supporting robot-assisted brain biopsy and the extent to which the scientific community has accepted the technique.MethodsThe Cochrane and PubMed databases were searched over a 30-year period between 1st of January 1988 and 31st of December 2017. Titles and abstracts were screened to identify publications that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 44 publications
5
51
0
1
Order By: Relevance
“…Using Equation (8), the required position of the platform can be calculated with respect to a given tissue target position as x ¼ x t r j j r t j j ; y ¼ y t r j j r t j j ; z ¼ z t r j j r t j j : (9) In order to manipulate the platform of the system to the desired position (Equation (9)), input values of θ 1 and θ 2 can be calculated from Equation (6).…”
Section: Structural Design and Kinematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using Equation (8), the required position of the platform can be calculated with respect to a given tissue target position as x ¼ x t r j j r t j j ; y ¼ y t r j j r t j j ; z ¼ z t r j j r t j j : (9) In order to manipulate the platform of the system to the desired position (Equation (9)), input values of θ 1 and θ 2 can be calculated from Equation (6).…”
Section: Structural Design and Kinematicsmentioning
confidence: 99%
“…The results of their work indicated that the designed system is capable of performing sophisticated operations due to its sufficient dexterity and stability. 9 As it can easily be seen in recent literature, assistive robotics in brain surgery shows promising and safe results. It should be noted that, for positioning, most of the utilized robotic systems still use classical industrial grade serial robot manipulators that are converted for general medical use.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of various surgical procedures undertaken in neurosurgery, highest benefits of robotic intervention can happen in functional neurosurgery. Though a plethora of robotic surgical programs exist, 8,[11][12][13][14] commercially available robots are few and far between. A relatively large number of stereotactic robotic programs have been documented in the literature.…”
Section: Robots In Functional Neurosurgerymentioning
confidence: 99%
“…Non-diagnostic samples in brain tumour biopsies are reported in up to 24% of cases and diagnostic errors in 10-30% of cases [2][3][4]9 . Various techniques are employed to improve the diagnostic value of brain biopsy methods [10][11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%